Architectural rendering of the Manufactures Building, Alaska Yukon Pacific Exposition, Seattle, 1908 - Nowell, Frank H., 1864-1950 (1908)
Photograph of architectural rendering. Title block on drawing: "End elevation. Manufactures Building. AYP Exposition, Seattle, Wash., Somervell and Cote, Architects. Building is being erected" PH Coll 727.437 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number